Imam al Tirmidhi and the Modern Age: An International Conference Tashkent, Uzbekistan, USSR Safar 24-27, 1411/September 14-17, 1990 (American Journal of Islam and Society, 1991)
The Muslim Religious Board for Central Asia and Kazakhstan organizedan international conference in Tashkent, the capital city of Uzbekistan, inconnection with the observances of the twelfth centenary of the birth of ImamAbu 'Isa Muhammad Ibn 'Isa al Tirmidhi, a native son. The conference wasattended by scholars from the Soviet Union and nearly 100 delegates fromoverseas.The keynote address, which was also the conference's theme, was deliveredThe American Journal of Islamic Social Sciences Vol. 8, No. 1 1991 185by the Board's Chairman Mufti Muhanunad Sadyq Muhammad Yusuf. Hepresented a detailed account of the Imam's work, e pecially the well-knownbook Al Jami' al Sahih, and its impact on the contemporary world.The scholars stressed the need for greater attention to research and studyof the Sunnah of the Prophet Muhammad (SAAS). They also adopted a numberof recommendations, including a call for greater attention to research on thehadith in order to facilitate its effective application in the everyday lives ofMuslims. This, it was observed, would contribute toward the assertion anddevelopoment of Islamic values throughout the ummah ...